Upaya Peningkatan Hasil Belajar Matematika dengan Menerapkan Model Pembelajaran Kooperatif Tipe Group Investigation pada Siswa Kelas X SMA Negeri 2 Gomo Tahun Pelajaran 2022/2023 - Salinudin Telaumbanua (Departement of Mathematics Education, 2024)
This research aims to find out: (1) describe the quality of mathematics learning by implementing the Group Investigation type cooperative learning model. (2) describe the results of mathematics learning by applying the Group Investigation type cooperative learning model. (3) significantly proves that the quality of mathematics learning is good by implementing the Group Investigation type cooperative learning model. (4) significantly proves that the average mathematics learning outcomes are good by applying the Group Investigation type cooperative learning model. This research was carried out at SMA Negeri 2 Gomo with the research subjects being students of class , consisting of 11 men and 9 women. The research carried out was classroom action research (PTK) which consisted of two cycles with Trigonometry material. Research instruments: (1) observation sheet, cycle I and cycle II consisting of (a) observation sheet for students who were not active in the learning process (b ) observation sheet for students who are actively involved in the learning process (c) observation sheet in the learning process of teacher respondents. (2) learning outcomes test, (3) learning quality questionnaire (4) interview guide sheet. Research results: (1) observation sheet for cycle I first meeting (a) students who were not active in the learning process were 30.8% (b) students who were actively involved in the learning process were 53.85% (c) observation sheet of respondents' learning process teachers was 61.11%, while in the first cycle of the second meeting (a) students who were not active in the learning process were 23.1% (b) students who were actively involved in the learning process were 64.42% (c) learning process observation sheet teacher respondents were 70.83%. Cycle II of the first meeting consisted of (a) students who were not active in the learning process were 19.2% (b) students who were actively involved in the learning process were 83.17% (c) teacher respondent learning process observation sheets were 83.33% , while in cycle II of the second meeting (a) students who were not active in the learning process were 11.5% (b) students who were actively involved in the learning process were 93.03% (c) teacher respondents' learning process observation sheet was 90.27 %. (2) mathematics learning outcomes using the Cooperative Group Investigation Type learning model in Cycle I, average 68.24; Completed 61.54%; Incomplete 38.46%; Standard Deviation 10.75 in Cycle II, average 84.96%; Completed 92.31%; Incomplete 7.69%; Standard Deviation 9.50. (3) the quality of Group Investigation Type Cooperative learning at meetings one to two in Cycle I was 80.42% in the good category, while in Cycle II it was 96.22% in the very good category.